Mortality and its associated factors among mechanically ventilated adult patients in the intensive care units of referral hospitals in Northwest Amhara, Ethiopia, 2023 - Tadesse, Eyob Eshete; Tilahun, Ambaye Dejen; Yesuf, Nurhusein Nuru; Nimani, Teshome Demis; Mekuria, Tesfaye Ayenew (Frontiers in Medicine, 2024)
Background: Worldwide, nearly half of the patients admitted to intensive care units require ventilatory support. Despite advances in intensive care unit patient management and mechanical ventilator utilization, the odds of mortality among mechanically ventilated patients are higher in resource-limited settings. Little is known about the mortality of patients on mechanical ventilation outside the capital of Ethiopia. This study aimed to assess mortality and its associated factors among mechanically ventilated adult patients in intensive care units.Method: Institutional-based cross-sectional study was conducted on mechanically ventilated patients in intensive care units from February 1, 2020, to March 1, 2023. Simple random sampling technique was used to select 434 patients' charts. A data extraction tool designed on kobo toolbox, a smartphone data collection platform, was used to collect the data. The data was exported into Microsoft Excel 2019 then into Stata 17 for data management and analysis. Descriptive statistics were used to summarize characteristics of the study participants. A bivariable logistic regression was conducted, and variables with P≤0.20 were recruited for multivariable analysis. Statistical significance was declared at p<0.05, and the strength of associations was summarized using an adjusted odds ratio with 95% confidence intervals. Result: A total of 404 charts of mechanically ventilated patients were included, with a completeness rate of 93.1%. The overall proportion of mortality was 62.87% with a 95% CI of (58.16-67.58). In the multivariable logistic regression, age 41-70 years (AOR: 4.28, 95% CI: 1.89-9.62), sepsis (AOR: 2.43, 95% CI: 1.08-5.46), reintubation (AOR: 2.76, 95% CI: 1.06-7.21), and sedation use (AOR: 0.41, 95% CI: 0.18-0.98) were found to be significant factors associated with the mortality of mechanically ventilated patients in the intensive care unit. Conclusion: The magnitude of mortality among mechanically ventilated patients was high. Factors associated with increased odds of death were advanced age, sepsis, and reintubation. However, sedation use was a factor associated with decreased mortality. The healthcare professionals in the intensive care units should give special attention for patients with sepsis, reintubation, sedation and who are older.